Forest, Brazil Nuts and Youth: Generational Transfer of Knowledge for the Development of Non-timber Forest Products in the Peruvian Amazon - (:unkn) unknown (My University, 2026)
The lack of clear and articulated strategies for the implementation of gender, intercultural and intergenerational approaches in the work carried out between state authorities, indigenous communities and families of Brazil nut collectors (and their cooper